2021
DOI: 10.1590/1807-1929/agriambi.v25n12p813-818
|View full text |Cite
|
Sign up to set email alerts
|

Genes highly overexpressed in salt-stressed Young oil palm (Elaeis guineensis) plants

Abstract: RNA-seq is a technique based on the large-scale sequencing of transcript-derived cDNAs using next-generation sequencing platforms mostly used today to characterize an organism’s transcriptome. The analysis of RNA-seq data allows for identifying genes differentially expressed in a given condition, such as salt stress. This study aimed to search and characterize genes from the African oil palm (Elaeis guineensis Jacq.) highly up-regulated during salt stress, with a long-term goal of gene promoter prospection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the case of oil palm, Refs. [6,18,19] reported the development of salinization protocols, which are necessary to study the response of E. guineensis to this abiotic stress in the search for some intraspecific trait variability. Such protocols are also needed to select tolerant oil palm genotypes developed via genetic engineering or genome editing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of oil palm, Refs. [6,18,19] reported the development of salinization protocols, which are necessary to study the response of E. guineensis to this abiotic stress in the search for some intraspecific trait variability. Such protocols are also needed to select tolerant oil palm genotypes developed via genetic engineering or genome editing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves harvested from control and stressed plants were immediately immersed in liquid nitrogen and stored at −80 • C until RNA extraction; three plants for treatments. Details regarding total RNA extraction and quality analysis, library preparation, and sequencing are in [15,19]. RNA-Seq raw sequence data are in the Sequence Read Archive (SRA) database of the National Center for Biotechnology Information (NCBI) under BioProject number PRJNA573093.…”
Section: Transcriptomics Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is another step in our work on characterizing the morphophysiological and molecular responses of oil palm plants to salinity stress [ 47 – 50 ]. Besides developing a salinization protocol successful in generating different levels of stress by gradients of electrical conductivity and water potential [ 47 ], the studies that followed up led to the identification of salt-responsive miRNAs and their putative target genes [ 48 ], as well as mapping the main pathways affected by this abiotic stress [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, we collected the apical leaves from three stressed plants (2.0 g NaCl, or ~ 40 dS m − 1 of electrical conductivity) at 05 and 12 days after the stress onset (DAT), together with the apical leaves from three control plants at 12 days (0.0 g NaCl, or ~ 2 dS m − 1 ), immediately frozen in liquid nitrogen and stored at − 80 °C until RNA-Seq. More details about the plant material, growth conditions, saline stress conditions, and the experimental design used in the study that generated this database were previously reported [ 47 – 50 ].…”
Section: Methodsmentioning
confidence: 99%